Influence of pH and precipitation temperature on the structural characteristics of aluminium hydroxides prepared form nitrate aqueous solutions - Vollet, D. R.; Donatti, D. A.; Domingos, R. N.; Camargo, H. (Editora Unesp, 1996)
Aluminium Hydroxides were precipitated from Aluminium Nitrate and Ammonium Hydroxide, at the temperatures 64 degrees C (hot) and 25 degrees C (cold), under the pH conditions 5, 7 and 9. The samples were characterized by X-Ray Diffraction (XRD) and Differential Thermal Analysis (DTA). The hydroxide precipitated at pH 9 and 64 degrees C is built up by pseudoboehmite and a minor share of others apparently amorphous hydroxides. The crystallinity of the hot yielded pseudoboehmite diminishes with the pH. The crystallite size was evaluated as about 40 Angstrom for the best crystallized sample. The cold precipitated product is apparently composed by amorphous or very poorly crystallized hydroxides. Upon heating, the cold precipitated hydroxides, and the low pH and hot precipitated hydroxide, release their structural water before the occurrence, about 430 degrees C, of the transition of the pseudoboehmite to gamma-alumina, and exhibit a shifting (towards low temperature side) and a broadening in the peak of the transition to alpha-alumina, which occurs at 1200 degrees C in the pseudoboehmite pattern. The yielded pseudo-boehmite peptized by HNO3, addition and gelified by evaporation in a critical concentration approximately 0.17 gcm(-3).
Keywords: boehmite; peptization; sol-gel; alumina